High-Sensitive CRP Correlates With the Severity of Liver Steatosis and Fibrosis in Obese Patients With Metabolic Dysfunction Associated Fatty Liver Disease - Zhu, Cuiling; Huang, Dongdong; Ma, Huihui; Qian, Chunhua; You, Hui; Bu, Le; Qu, Shen (Frontiers in Endocrinology, 2022)
Background: Metabolic dysfunction associated fatty liver disease (MAFLD) is the commonest hepatopathy worldwide due to the obesity epidemic and associated with chronic low-grade inflammation. High-sensitive C-reactive protein (hsCRP) as an inflammatory marker has been used in diagnosing MAFLD. However, the association between hsCRP and the severity of liver steatosis and fibrosis among obese patients with MAFLD remains to be elucidated. Objective: To explore the correlation of hsCRP with the severity of liver steatosis and fibrosis among Chinese obese patients with MAFLD. Methods: A total of 393 obese patients with mean BMI 34.8 ± 6.6 kg/m2 were selected and categorized as MAFLD and Non-MAFLD group. Anthropometric data, biochemical indices, and hsCRP were measured. The severity of hepatic steatosis and fibrosis was assessed using FibroScan. Multivariate logistic regression analysis was performed to determine the relationship between hsCRP and the risk of MAFLD and its disease severity. Results: Patients with MAFLD showed significantly elevated hsCRP levels and were more likely to have severe steatosis and fibrosis compared to those without MAFLD. The proportions of MAFLD, severe steatosis, and severe fibrosis were significantly increased across the hsCRP quartiles (P-trend = 0.004, 0.021, and 0.006, respectively). After multivariable adjustments, the adjusted ORs (AORs) and 95%CI for MAFLD was 1.00 (reference), 1.298 (0.587-2.872), 2.407 (1.002-5.781), and 2.637(1.073-6.482) (Q1-Q4, P-trend = 0.014). Likewise, the AORs (95%CI) for severe steatosis and severe fibrosis were remarkably increased with the increment of serum hsCRP quartiles (P-trend < 0.001, P-trend = 0.021, respectively). Conclusions: Elevated serum hsCRP levels were associated with increased risk of MAFLD among Chinese obese patients, and correlated positively with the severity of liver steatosis and fibrosis, suggesting that hsCRP can be used as a potential biomarker to monitor and predict disease severity among Chinese obese population with MAFLD.